Toward Precision Vaccinology for Mpox: Rational Antigen Design, Next-Generation Platforms, and Immune Correlates of Protection - Yithenthrathevinair K Paramasivam; Nur Syafiqah Mohamad Nasir; Mohd Zulkifli Salleh (Tropical Medicine and Infectious Disease, 2026)
Mpox has emerged as a global public health concern, highlighting the limitations of traditional vaccinia-based vaccination strategies and the urgent need for precision vaccinology approaches. Advances in structural virology and immunoinformatics have enabled the identification of conserved immunodominant antigens from both mature virion and extracellular virion forms, supporting the development of multivalent antigen combinations capable of inducing broad neutralizing antibody (nAb) responses. Emerging delivery technologies including mRNA-lipid nanoparticles, viral vectors, and self-assembling protein nanoparticles offer rapid scalability, enhanced immunogenicity, and improved safety compared with conventional live-attenuated vaccines. Addressing antigenic evolution, vaccine supply limitations, and population-specific immune variability will be crucial for optimizing vaccine effectiveness. This review synthesizes current evidence on antigen design, vaccine delivery platforms, and immunological correlates of protection to outline a framework for next-generation mpox vaccines. Precision vaccinology therefore represents a transformative strategy for developing durable, clade-specific mpox vaccines and strengthening preparedness against future orthopoxvirus outbreaks worldwide.